Clinical Pathways For Pancreatic Surgery: Are They A Suitable Instrument For Process Standardization To Improve Process And Outcome Quality Of Patients Undergoing Distal And Total Pancreatectomy? - A Retrospective Cohort Study - Téoule P; Römling L; Schwarzbach M; Birgin E; Rückert F; Wilhelm TJ; Niedergethmann M; Post S; Rahbari NN; Reißfelder C; Ronellenfitsch U (Dove Medical Press, 2019)
Patrick Téoule,1 Laura Römling,1 Matthias Schwarzbach,2 Emrullah Birgin,1 Felix Rückert,1 Torsten J Wilhelm,3 Marco Niedergethmann,4 Stefan Post,1 Nuh N Rahbari,1 Christoph Reißfelder,1 Ulrich Ronellenfitsch5 1Department of Surgery, Universitätsmedizin Mannheim, Medical Faculty Mannheim, Heidelberg University, Mannheim 68167, Germany; 2Department of General, Visceral, Vascular, and Thoracic Surgery, Klinikum Frankfurt Höchst, Frankfurt 65929, Germany; 3Department of General and Visceral Surgery, GRN-Klinik Weinheim, Weinheim 69469, Germany; 4Department of Surgery, Alfried Krupp Hospital, Essen 45131, Germany; 5Department of Visceral, Vascular and Endocrine Surgery, University Hospital Halle, Halle, GermanyCorrespondence: Ulrich RonellenfitschUniversity Hospital Halle, Department of Visceral, Vascular and Endocrine Surgery, Ernst-Grube-Street 40, Halle (Saale) 06097, GermanyTel +49 345 557 2314Fax +49 345 557 2551Email ulrich.ronellenfitsch@uk-halle.dePurpose: Pancreatic surgery demands complex multidisciplinary management, which is often cumbersome to implement. Clinical pathways (CPs) are a tool to facilitate this task, but evidence for their utility in pancreatic surgery is scarce. This study evaluated if CPs are a suitable tool for process standardization in order to improve process and outcome quality in patients undergoing distal and total pancreatectomy.Patients and methods: Data of consecutive patients who underwent distal or total pancreatectomy before (n=67) or after (n=61) CP introduction were evaluated regarding catheter management, postoperative mobilization, pancreatic enzyme substitution, resumption of diet and length of stay. Outcome quality was assessed using glycaemia management, morbidity, mortality, reoperation and readmission rates.Results: The usage of incentive spirometers for pneumonia prophylaxis increased. The median number of days with hyperglycemia decreased significantly from 2.5 to 0. For distal pancreatectomy, the incidence of postoperative diabetes dropped from 27.9% to 7.1% (p=0.012). The incidence of postoperative exocrine pancreatic insufficiency decreased from 37.2% to 11.9% (p=0.007). There was no significant difference in mortality, morbidity, reoperation and readmission rates between groups.Conclusion: Following implementation of a pancreatic surgery CP, several indicators of process and outcome quality improved, while others such as mortality and reoperation rates remained unchanged. CPs are a promising tool to improve quality of care in pancreatic surgery.Keywords: clinical pathways, pancreatic surgery, distal pancreatectomy, pancreatectomy, quality of care